Generalist managers and firm innovation worldwide: The role of innovation-specific institutions - Wu, Yue Rio; Huang, Sterling; Tsang, Albert; Wang, Kun Tracy (Journal of Accounting and Economics, 2025)
We examine how generalist CEOs influence innovation outcomes across 25 countries from 2001 to 2019. We assemble a novel, extended dataset of generalist CEOs and find that generalist CEOs positively affect innovation, particularly in countries with abundant innovation resources. This finding aligns with the notion that generalist CEOs leverage their broad knowledge and cross-industry experience to integrate resources across institutional environments, thereby fostering innovation activities. However, in countries with stricter patent systems, the increased need for specialized knowledge and resources limits the value that generalist CEOs can contribute, leading to decreased innovation activities. Our research highlights how institutional environments shape the efficacy of CEO human capital in driving innovation, thus offering insights for the design of innovation policies that maximize leadership potential across different institutional contexts.